Analisa Kepuasan Pelanggan Pelayanan Kesehatan Menggunakan Metode Potential Gain in Customer Value (PGCV) Pada Klinik Ade Elisa Kabupaten Deli Serdang - Hutagalung, Sandro Andika; Delvika, Yuana; Sutrisno, Sutrisno (Universitas Medan Area, 2024)
Satisfaction is a person's feeling of pleasure or disappointment after comparing the performance (results) of the product thought to the expected performance (work performance). If the performance is under expectations, it means the customer is not satisfied; vice versa, it will cause the patient to lose interest in seeking treatment. To find out the priority level in improving the quality of clinical patient services, it used the Potential Gain in Customer Value (PGCV) method. Then, to identify dimensions of service quality, it used the Importance Performance Analysis (IPA) method. The data collected in this study were by conducting surveys, distributing questionnaires, and interviewing. The result of the servqual score was negative, with the largest gap score in the attribute (Responsiveness 1)-Affordable inspection fees, and the attribute (Emphaty3)-Nurse was always there when the patient called or needed with a score of -1.73333. The attribute Responsiveness 1 (Affordable examination fee) with the largest PGCV index score of 10.9333. The second priority that had to be improved with the PGCV index score was 10.69445. The attribute Rb3 (Take action according to the procedure) was the third-highest priority that had to be improved with a PGCV index score of 10.166667.